In Vitro Phytotoxicity and Antioxidant Activity of Selected Flavonoids - De Martino, Laura; Mencherini, Teresa; Mancini, Emilia; Aquino, Rita Patrizia; Rolim de Almeida, Luiz Fernando [UNESP]; De Feo, Vincenzo (Mdpi Ag, 2012)
The knowledge of flavonoids involved in plant-plant interactions and their mechanisms of action are poor and, moreover, the structural characteristics required for these biological activities are scarcely known. The objective of this work was to study the possible in vitro phytotoxic effects of 27 flavonoids on the germination and early radical growth of Raphanus sativus L. and Lepidium sativum L., with the aim to evaluate the possible structure/activity relationship. Moreover, the antioxidant activity of the same compounds was also evaluated. Generally, in response to various tested flavonoids, germination was only slightly affected, whereas significant differences were observed in the activity of the various tested flavonoids against radical elongation. DPPH test confirms the antioxidant activity of luteolin, quercetin, catechol, morin, and catechin. The biological activity recorded is discussed in relation to the structure of compounds and their capability to interact with cell structures and physiology. No correlation was found between phytotoxic and antioxidant activities.
Keywords: flavonoids; germination; radical elongation; antioxidant activity; structure/activity